Antibody elution with 2-me/SDS solution: Uses for multi-layer immunohistochemical analysis of wholemount preparations of human colonic myenteric plexus - Adam Humenick; M.E. Johnson; B.N. Chen; M. Wee; D.A. Wattchow; M. Costa; P.G. Dinning; S.J.H. Brookes (Heliyon, 2024)
Indirect immunofluorescence is usually restricted to 3-5 markers per preparation, limiting analysis of coexistence. A solution containing 2-mercaptoethanol and sodium dodecyl sulfate (2-ME/SDS) can elute indirect immunofluorescence labelling (i.e. primary antisera followed by fluorophore-conjugated secondary antisera) and has been used for sequential staining of sections. The aim of this study was to test whether 2-ME/SDS is effective for eluting indirect immunofluorescent staining (with primary antisera visualised by fluorophore-coupled secondary antisera) in wholemount preparations. We also analysed how 2-ME/SDS may work and used this understanding to devise additional uses for immunofluorescence in the nervous system. 2-ME/SDS appears to denature unfixed proteins (including antisera used as reagents) but has much less effect on antigenicity of formaldehyde-fixed epitopes. Moieties linked by strong biotin-streptavidin bonds are highly resistant to elution by 2-ME/SDS. Two primary antisera raised in the same species can be applied without spurious cross-reactivity, if a specific order of labelling is followed. The first primary antiserum is followed by a biotinylated secondary, then a tertiary of fluorophore-conjugated streptavidin. The preparation is then exposed to 2-ME/SDS, which has minimal impact on labelling by the first primary/secondary/tertiary combination. However, when this is followed by a second primary antiserum (raised in the same species), followed by a fluorophore-conjugated secondary antiserum, the intervening 2-ME/SDS exposure prevents cross-reactivity between primary and secondary antisera of the two layers. A third property of 2-ME/SDS is that it reduces lipofuscin autofluorescence, although it also raises background fluorescence and strongly enhances autofluorescence of erythrocytes. In summary, 2-ME/SDS is easy to use, cost-effective and does not require modified primary antisera. It can be used as the basis of a multi-layer immunohistochemistry protocol and allows 2 primary antisera raised in the same species to be used together.